What happened on Blackstone Avenue? Recovering the origins of the coase theorem - Steven G. Medema (Duke University, Center for the History of Political Economy (CHOPE), 2023)
This paper revisits the path by which Coase developed the result now known as the Coase theorem, including the famous meeting at the home of Aaron Director during which Coase 'converted' a group of Chicago economists to his way of thinking. Drawing on published and archival sources, we discuss the challenges that Coase encountered in formulating his argument, particularly as regards the impact of transaction costs on his negotiation result, and illuminate the roles of Duncan Black and David Cavers in nudging Coase toward a theoretically valid result. Finally, we show that the Chicago economists' 'conversion' was both less extensive than commonly believed and likely involved a their acceptance of a result that is both demonstrably incorrect and fundamentally different from that which Coase published in 1960.
Keywords: K00; H2; D62; B2; 330; Coase theorem; Ronald Coase; externalities; market failure; transaction costs